The Natural and the Social Pakistan: An Eco-Marxist Perspective of Tariq Rahman's Animals - Irshad, Wafa; Ali, Sajid (Annals of Human and Social Sciences, 2025)
Pakistani literature has contributed to the ongoing debate on the environmental crisis. However, the scholarly works around the writings rarely address the importance of the environment and its influence on human and non-human relationships. This study addresses this issue through textual analysis of Tariq Rahman’s “Animals” using Eco-Marxism. The story critiques capitalist-driven environmental exploitation, where land and animals are commodified under the guise of progress. The bourgeoisie benefit from development projects, and the proletariat suffer exploitation from both the elites and environmental degradation. The study finds that “Animals” exposes capitalist exploitation of both nature and labor, reinforcing systemic inequality. Rahman illustrates that environmental degradation is not incidental but a consequence of commodification that can be solved by giving importance to indigenous culture. Future studies calls for research addressing marginalization, resistance, and equitable development in Pakistani literature